Android Learning Media Training Evaluation With The Kirkpatrick Analysis Method In Elementary School - Bakhri, Syaiful (Mudir : Jurnal Manajemen Pendidikan, 2023)
The world has entered an increasingly sophisticated era. All sectors are competing to upgrade their digital capabilities to be able to compete globally, including the education sector. The rapid development of technology requires the education world to upgrade its knowledge in order to improve its quality. Therefore, new learning methods are needed that are in line with the times, such as using IT-based learning media. However, the utilization of IT-based learning media at SDN Ngaliyan 01 is not yet optimal due to a lack of human resources skilled in that field. This research discusses the use of android-based learning media (guess image and find words game), with the aim of improving information technology competence in the field of education for teachers and providing a fun learning experience for students to make it easier to understand the lessons, because visual media is generally easier to understand than conventional media. Then, the game can also improve students' analytical skills through problem-solving with the guess image and find words game. The method used in this study is descriptive analysis method, in which the data obtained is processed, described, and analyzed. The stages of this training consist of 4 stages: preparation which includes observation, implementation which includes (making android application content, android learning media training, making learning applications with android), and evaluation using Krickpatrick analysis method, including (measurement of level 1 (reaction) and measurement of level 2 (learning)). The results of this android-based learning media training evaluation showed that the competence of the SDN Ngaliyan 01 Semarang teachers increased, as evidenced by the measurement of competence through the Kirkpatrick Analysis method at level 1 (reaction), where the participants understood the process of making the android application guess image & find words game, and measurement of level 2 (learning), where there was an increase in the average pre-test and post-test results, which means that the participants gained new knowledge related to the making of android-based learning media applications.